Vertisoles y cerámica indígena: un estudio de procedencia basado en DRX, sitio Guayacas (Paysandú, Uruguay) - Irina Capdepont; Gustavo Piñeiro (Revista del Museo de Antropologia, 2010)
The most abundant archaeological record in the middle and late Holocene in the litoral region of Uruguay is formed by ceramic materials. Previous information usually comes from macroscopic studies, oriented to the reconstruction of decorative styles, forms, and technology. This paper presents XRD analyses of archaeological ceramics from Guayacas site (Department of Paysandú ). This study seeks to complement the knowledge about the first stage of the process of manufacture: the selection of raw materials. In order to do this, an XRD analysis is also carried out on sediments and outcrops in the area, as well as on sediments from an archaeological excavation. Results indicate that the paste of ceramic materials is uniform and lacks illite-like minerals. The anthropogenic soils present smectite, quartz, illite and mixed clays; the natural soils and outcrops are dominated by smectite and quartz. One of these soils is proposed as a potential source of local raw material. The data obtained provide new information for the understanding of the area of occupation on the Daymán river during the late Holocene